Plant-derived Hepatoprotective Drugs - Kumar Jain, Sachin; Kumar Sahu, Ram; Soni, Priyanka; Soni, Vishal; Shankar Shukla, Shiv (Bentham Science Publishers, 2023)
Plant-derived Hepatoprotective Drugs is a comprehensive guide that explores the world of medicinal plants and their hepatoprotective properties, offering both basic and applied insights for scholars and hepatology residents. Structured chapters provide a deep dive into the subject, while referencing relevant research and future perspectives. Readers will learn the science behind hepatotoxicity and the role of plants in safeguarding liver health. The book also helps researchers to explore bioactive compounds extracted from plants, along with herbal formulations that contribute to hepatoprotection, and conveys an understanding of the effects of edible plants and spices on liver wellness. A chapter focusing on isolation and characterization of phytochemicals bridges theory and application for discovering and developing hepatoprotective biopharmaceuticals. Key Features: Gives a thorough understanding of hepatotoxicity and related bioactive compounds Comprehensive references to enhance understanding Well-structured chapters providing organized knowledge Basic and applied information for diverse readers Future perspectives offering a glimpse into ongoing research This is an ideal reference for pharmacology scholars and residents in hepatology, as well as readers interested in nature's potential in promoting liver health.